PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (SURVEI PELANGGAN SUZUKI, DEALER FATMAWATI, JAKARTA SELATAN) - Mohamad Rizan; Fajar Andika (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
The objective of this study is to describe clearly about product quality, service quality and customer satisfaction in dealer Suzuki Fatmawati, Jakarta Selatan. The method is descriptive and explanatory research survey. The samples taken are customers who do service in dealer Suzuki Fatmawati, Jakarta Selatan, with 225 respondents. The sampling technique used purposive sampling, research instruments is to use questionnaires, and using multiple linear regression analysis. The result of this descriptive study is product quality variable and service quality variable influence customer satisfaction variable. Results of hypothesis testing showed: 1) Product quality variable negatively affect customer satisfaction variables, 2) Service quality variable has positive influence on customer satisfaction variable; 3) This study shows that the percentage contribution of the influence of independent variables (product quality and service quality) to the dependent variable (customer satisfaction) of 5.6% (R Square).Keyword: Product Quality, Service Quality, Customer Satisfaction